2015
DOI: 10.1074/jbc.m115.680686
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Region of the Ubiquitin Regulatory X (UBX) Domain-containing Protein 1 (UBXD1) Modulates Interdomain Communication within the Valosin-containing Protein p97

Abstract: Background: p97 cooperates with cofactors to control various aspects of cellular homeostasis. Mutations at the interdomain interface cause a multisystem degenerative disorder. Results: We identified three binding epitopes on p97 for the N-terminal domain of cofactor UBXD1 (UBXD1-N), including disease-associated residues. Binding reduced p97 ATPase activity. Conclusion: UBXD1-N modulates interdomain communication and activity of p97. Significance: The polyvalent binding mode defines a new subset of p97 cofactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 57 publications
4
39
0
Order By: Relevance
“…Larger shifts are observed for V68 and I175 that report on VIM binding, from which a true0Kd value of 22 ± 2 µM for the VIM-NTD interaction is calculated (see Materials and methods Figure 7—figure supplement 3). This value is in good agreement with affinities measured for the binding of full-length wt p97 to full length UBXD1, 3.5 µM (Hänzelmann and Schindelin, 2011), and for the binding of the isolated NTD with UBXD1-N, 9 µM (Trusch et al, 2015), especially considering that the latter pair of studies were carried out at 25°C in comparison to 50°C for the NMR results reported here. Studies of R155H and N387H mutants of ND1Lp97-ADP that mildly perturb the up/down equilibrium (Figure 7C, Figure 7—figure supplement 2D) show that two-pronged binding involving VIM and H1/H2 occurs partially but that a complete down conformation is not obtained with a 3-fold excess of adaptor over p97 protomer (compare dashed and solid arrows that correspond to movements for peaks from wt and mutant p97, respectively).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Larger shifts are observed for V68 and I175 that report on VIM binding, from which a true0Kd value of 22 ± 2 µM for the VIM-NTD interaction is calculated (see Materials and methods Figure 7—figure supplement 3). This value is in good agreement with affinities measured for the binding of full-length wt p97 to full length UBXD1, 3.5 µM (Hänzelmann and Schindelin, 2011), and for the binding of the isolated NTD with UBXD1-N, 9 µM (Trusch et al, 2015), especially considering that the latter pair of studies were carried out at 25°C in comparison to 50°C for the NMR results reported here. Studies of R155H and N387H mutants of ND1Lp97-ADP that mildly perturb the up/down equilibrium (Figure 7C, Figure 7—figure supplement 2D) show that two-pronged binding involving VIM and H1/H2 occurs partially but that a complete down conformation is not obtained with a 3-fold excess of adaptor over p97 protomer (compare dashed and solid arrows that correspond to movements for peaks from wt and mutant p97, respectively).…”
Section: Resultssupporting
confidence: 90%
“…For wt, moderate (R155H and N387H) and severe (R95G, R155P) mutants, true0K1 << 1, true0K1 ~ 0.15, true0K1 ~ 1, respectively (Figure 6). A value of true0K2 ~ 200 µM has been measured, as described above, and although a value for K 3 is not available from our studies (too weak) it has been measured to be approximately γ=25 fold larger than true0K2 in studies of an isolated NTD (Trusch et al, 2015). We have carried out simulations assuming true0K5=0.1 (wt), true0K5=0.5 (R155H, N387H) and true0K5=10 (R95G, R155P) ( i.e ., locking of the NTD becomes progressively more difficult with severity of mutation), with true0K3 and true0K4 obtained from true0K2=K3/γ and true0K4=K5/γ, respectively, assuming γ=25 for wt and γ increasing for the mutants in proportion to true0K5(mutant)/true0K5(wt) so that true0K2 and true0K4 are fixed (microscopic binding of VIM unperturbed by mutation).…”
Section: Methodsmentioning
confidence: 60%
See 3 more Smart Citations